2-Bromo-4,5-Dimethoxy Chalcone Inhibits Cisplatin-induced LLC-PK1 Kidney Cell Death - Lee, Dahae; Lee, Heesu; Kang, Ki Sung; Lee, Jae Wook (대한화학회, 2018)
The kidney has various functions, including modulating blood pressure, balancing electrolytes, and controlling blood volume. Among these functions, extracting metabolic waste from blood plays an important role in kidney. 1,2 Additionally, kidney epithelial cells are vulnerable to the toxic effects of various chemical agents and medications. 3,4 Recently, cisplatin, an inorganic platinum-based chemotherapeutic agent, has been used to inhibit solid malignant tumors due to its high therapeutic potential. 5,6 However, continuous exposure to cisplatin can cause various significant side effects, such as bone marrow suppression, peripheral neuropathy, and nephrotoxicity. In particular, a single dose of cisplatin treatment can cause nephrotoxicity among one-third of patients.(7-9) Therefore, it has been suggested to develop medication for cisplatin-induced nephrotoxicity.